WASTE MANAGEMENT OF DISPOSABLE MEDICAL MASK IN SELOREJO VILLAGE, BLITAR - Adistha Eka Noveyani; Dimas B. C. Wicaksono; Yunus Ariyanto; Tania Hesti Novitasari; Tri Valda Gilby Renata; Alifia Sharfina; Anisa Kusumaningsih; Aghnes Widayanti (UNEJ e-Proceeding, 2022)
There were disposable masks waste that are disposed of carelessly in the Perhutani area of the Selorejovillage. In addition, residents did not know how to process mask waste. There was also a lack ofdiscipline in the use of proper masks and low awareness of hand washing. Following up on these results,solutions that could be done weretraining on how to wear masks correctly, training on 6 steps ofwashing hands,training on waste management of disposable masks. Coordination was carried out withlocal working groups and community leaders, the head of the RT and the head of the RW. Theimplementation of training activities is carried out online, but the implementation of pre-test and posttest,evaluation of self-practice,also documentation is carried out offline. Citizen participation is quitegood, but still needs to be improved, especially when conducting online discussions. Training on usingmasks correctly showed an increase in knowledge of 93%. Training on with 6 steps of washing handswith soap showed an increase in knowledge of 91.8%. Lastly, Training on the waste management ofdisposable masks showed an increase in knowledge of 89.1%, where these indicators has exceeded thetargeted indicators.Keywords: disposable mask, waste management, training, covid-19